Frontiers in Geotechnical Engineering - Latha G., Madhavi (Developments in Geotechnical Engineering, 2019)
This volume contains contributions by eminent researchers in the field of geotechnical engineering. The chapters of this book are based on the keynote and theme lectures delivered at the Indian Geotechnical Conference 2018, and discuss the recent issues and challenges, while providing perspective on the possible solutions and future directions. A strong emphasis is placed on proving connections between academic research and field practice, with many examples and case studies. Topics covered in this volume include contemporary infrastructural challenges, underground space utilization, sustainable construction, dealing with problematic soils and situations and geo-environmental issues including landfills. This book will be of interest to researchers, practitioners and students alike.